Evaluation of maton rockphosphate in the acid rice soils of Kerala - Suja Thomas (Department of Soil Science and Agricultural Chemistry, College of Horticulture, 1997)
A study conducted at College of Horticulture during the period 1994 – 96 so as to assess the effectiveness of Maton rockphosphate (MTRP) as a source of P compared with single super phophate (SSP), diammonium phosphate (DAP) and Mussoorie rockphosphate (MRP). In addition to the above sources a control treatment (with no P fertiliser) and another treatment with SSP at the rate of 45 kg P2o5 ha-1 given twice (conventional practice) were also included. The P release from all the sources were monitored with an incubation experiment. In order to evaluate the response of fertilisers two continuous pot culture experiments were undertaken using Jaya variety of rice. Two acid rice soils of Kerala, viz., Kuttanad alluvium and laterite were used for the study. The variations in pH of the soil types indicated that there was increase with advancement of periods under waterlogging irrespective of the treatments including the control. Available N was high in Kuttanad alluvium as compared to laterite and was found to decrease with periods of incubation. The content of available P gradually increased with period of incubation, reached a peak at 120 days for water soluble phosphates (SSP and DAP) and 180 days for rockphosphates, irrespective of the soil types. Comparing the two extractants, Mathewstriacid extracted more available P than that of the Bray solution in both the soil types. Available K decreased with periods of incubations. In general, Kuttanad alluvium recorded higher content of available nutrients as compared to laterite. In both the soil types the most dominant P fraction was Fe – P followed by AI – P and Ca – P. While evaluating the pot culture experiment it was observed that available nutrient content decreased with advancement of crop growth. Even after the harvest of second crop, the residual effect of MTRP was recorded to be high. There was maximum uptake of P at the second crop season as compared to the first crop irrespective of the soil types. The leachate loss decreased with crop growth in both the soil types. But the maximum leachate loss was recorded for N followed by K and P. The grain yield as well as the relative yield was found to be maximum for the laterite soil on comparison to Kuttanad alluvium for the first and second crop of rice. In Kuttanad alluvium, DAP and MTRP yielded better in the first and second crop respectively. While in laterites SSP was found to be better in grain yield as compared to other sources, The source, DAP was superior to others in straw yield for both the soil types with increase in levels of P application, there was increase in grain and straw yield.